Risk prediction models for extubation failure in critically ill patients on mechanical ventilation: a systematic review - Zeng, Xiang; Chen, Xiao Juan; Lai, Ping; Chen, Jie; Chen, Zhoujing; Qi, Xiyu (Frontiers in Medicine, 2025)
BackgroundFailure to extubate successfully from mechanical ventilation is a critical event associated with poor prognosis in ICU patients, significantly prolonging hospital stays and increasing mortality rates. It is widely accepted in academic circles that developing prediction models for extubation failure can facilitate precise extubation decisions. Despite the rapid proliferation of relevant prediction models, their methodological quality and bedside applicability remain ambiguous.ObjectiveThis study aims to outline the predictive factors associated with the risk of extubation failure in patients undergoing mechanical ventilation in the Intensive Care Unit (ICU) and to summarize the existing predictive models.MethodsWe searched the China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, China Biomedical Database, PubMed, Embase, Web of Science, and Cochrane Library. We included both prospective and retrospective studies that developed or validated risk prediction models for extubation failure in patients undergoing mechanical ventilation in the ICU. The Prediction Model Risk of Bias Assessment Tool (PROBAST) was used to assess the bias and applicability of the models.ResultsThis analysis includes 14 studies. Frequency analysis of the predictors revealed that there are 15 predictors that appeared at least twice, among which mechanical ventilation duration, GCS score, APACHE II score, age, and hemoglobin were the most common predictors. From the perspective of the models, only 2 studies conducted both internal and external validation, 3 studies ultimately employed machine learning, while 11 studies utilized traditional modeling methods. However, we found that many studies faced issues such as insufficient sample sizes, missing crucial methodological information, and all models being rated as having a high risk of bias.ConclusionMost published predictive models lack methodological rigor, leading to a heightened risk of bias. Future research should prioritize the enhancement of methodological rigor and the external validation of risk prediction models for extubation failure in ICU patients receiving mechanical ventilation. Additionally, it is essential to emphasize adherence to scientific methods and transparent reporting to improve the accuracy and generalizability of research findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, Registration number:CRD420251124371.